2020
DOI: 10.1088/1361-6560/abc5a7
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact optical imaging of brain hemodynamics in preterm infants: a preliminary study

Abstract: Extremely preterm infants’ hemodynamic instability places them at high risk of brain injury. Currently there is no reliable bedside method to continuously monitor cerebral hemodynamics in the neonatal intensive care unit (NICU). This paper reports a feasibility study to adapt and test an innovative speckle contrast diffuse correlation tomography (scDCT) device for noncontact, high-density, 3D imaging of cerebral blood flow (CBF) in preterm infants. The scDCT scans a focused point near-infrared illumination to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 51 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…In addition to this preclinical study, our scDCT has been tested for noninvasive imaging of human preterm brains [38] and human mastectomy skin flaps [36, 78, 79] with a penetration depth of ~10 mm. This depth (10 mm) enables penetrating deeply into human infant brains [38]. We are currently optimizing the system (e.g., wavelengths/powers of laser diodes and sensitivities of cameras) to penetrate deeper with the goal of imaging human adult brains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this preclinical study, our scDCT has been tested for noninvasive imaging of human preterm brains [38] and human mastectomy skin flaps [36, 78, 79] with a penetration depth of ~10 mm. This depth (10 mm) enables penetrating deeply into human infant brains [38]. We are currently optimizing the system (e.g., wavelengths/powers of laser diodes and sensitivities of cameras) to penetrate deeper with the goal of imaging human adult brains.…”
Section: Discussionmentioning
confidence: 99%
“…We have preliminarily tested the scDCT for imaging blood flow distributions in tissue/head‐simulating phantoms, rodent brains, and other human tissues including forearm muscles, burn wounds, and mastectomy skin flaps under various medical conditions [31, 35–37]. Very recently, we conducted a preliminary study to test two preterm infant cases in the NICU by scDCT [38]. However, no pathology can be induced in human subjects to comprehensively test the feasibility and accuracy of the device for continuous CBF imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In benefitting from 2D cameras, these approaches are akin to SCOS/DSCA (diffuse speckle contrast analysis), which measures BFI from homodyne speckle contrast(s). 11 , 55 58 MiDWS and SCOS/DSCA are compared for human brain BFI measurements in Table 2 .…”
Section: Core Principlesmentioning
confidence: 99%
“…In benefitting from 2D cameras, these approaches are akin to SCOS/DSCA (diffuse speckle contrast analysis), which measures BFI from homodyne speckle contrast(s). 11,[55][56][57][58] MiDWS and SCOS/DSCA are compared for human brain BFI measurements in Table 2. Is it possible to obtain TOF information while benefitting from the scalability of 2D interferometric approaches?…”
Section: D Camera Interferometric Approachesmentioning
confidence: 99%
“…We recently developed an innovative, noncontact, camera-based speckle contrast diffuse correlation tomography method for high-density imaging of blood flow distributions in deep tissues (up to approximately 10 mm). [10][11][12][13][14][15][16][17][18][19] Case studies with speckle contrast diffuse correlation tomography were reported for three-dimensional imaging of blood flow distributions in brain, wound/burn tissues, and mastectomy skin flaps. [10][11][12][13][14][15][16][17][18] In this preliminary study, a small group of patients undergoing mastectomies were imaged sequentially by dye-free speckle contrast diffuse correlation tomography and dye-based commercial fluorescence angiography (SPY-PHI; Novadaq/Stryker, Kalamazoo, Mich.) to identify ischemic tissues in mastectomy skin flaps.…”
mentioning
confidence: 99%